USTĄPIENIE POLITYKA - NORMALNY PROCES W DEMOKRACJI - Joerden, Jan C. (Wydział Prawa i Administracji UAM, 1998)
Within the framework of evaluating political steps forcing a retirement of a politician the Author of the article has distinguished three kinds of rules: a) rules of behaviour that indicate what kind o f behaviour is desirable and what kind is not. These rules relate first of all to penal law and ethics: perspectively they serve to steer a behaviour and retrospectively - to evaluate an example of concrete behaviour post factum-, b) rules of imputation which - generally speaking - assume a function of attaching some true past event to a person who shall be charged with responsibility for it (in penal law - rules that make it possible to distinguish between perpetration of a crime and participation in it); c) rules of proceeding which inform us about ways o f application (who? how?) of the two precedent rules. The Author discusses in detail all these rules and illustrates them with examples taken mostly from German political life.
RETIREMENT OF A POLITICIAN - SOMETHING NORMAL IN DEMOCRACY